Online banking in Serbia: An analysis of consumer preferences and the need for traditional banking services - Lukić Nikolić Jelena (Bankarstvo, 2025)
This paper discusses the fundamental elements of online banking in Serbia, with an emphasis on user demographics, preferences, and the frequency with which they need to physically visit bank branches. The survey gathered 209 responses between August and December 2024. Although online banking is growing increasingly popular, physical presence in banks has not faded entirely, as many customers continue to visit banks for certain services. The Mann-Whitney test results revealed that respondents' gender is not a statistically significant factor in the frequency with which they visit banks. On the other hand, the Kruskal-Wallis test results revealed that age had a significant impact on the frequency of visits to bank branches, with older respondents visiting the banks more frequently. In addition, there are statistically significant differences in respondents' educational levels, with those with greater education visiting banks more frequently. The study's findings provide important guidance for banks on how to build digital services while remaining competitive in the market.